Re-Evaluate Interrelationship Dose-Response of Diminazene Aceturate Against to Infected Mice of Trypanosoma Evansi Bangkalan Isolates - Lazuardi, Muchamad; Wahyudi, Muhamad Teguh; Munier, Ratna Sofaria (Jurnal Veteriner; Vol 14 No 2 (2013), 2013)
In vivo drug experiment involving Trypanosoma evansi (T.evansi) of Bangkalan isolated from outbreakof surra at 1988 in Madura Island, (Indonesia) infected mice  were performed. Single dose of diminazeneaceturate at the range of dose 5.0 to 9.7 mg/kg bw intra peritoneal were tested against 4th parasitaemicgrade level of infected mice. The assesment of trypanocide dose was using  probit test analysis at confidenceinterval  95% after observing trial groups data from thick blood smear examination of vein tail. Apparentlythe dose of diminazene at  6.858 mg/kg bwt had eliminated 50% of the bloodstream parasites and 9.138mg/kg bw for  99% had eliminated parasites. The research result indicates that Bangkalan isolate of T.evansi had expressed reduced susceptible to diminazene more than 1.3 times than regimentation dose toresearch report on 2005 year at the same research subject namely mice (at about 5.22 mg/kg bw).
Keywords: surra, chemotrypanocide, interchalating, kinetoplast, variant surface glycoproteins